ANALISIS PERSEPSI PETANI KELAPA SAWIT SWADAYA BERSERTIFIKASI RSPO DALAM MENGHADAPI KEGIATAN PEREMAJAAN PERKEBUNAN KELAPA SAWIT DI KECAMATAN UKUI KABUPATEN PELALAWAN - Hutasoit, Farmelia R; Hutabarat, Sakti; Muwardi, Didi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Oil palm is an  important vegetable oil in various products including food, non-food, and biodiesel. Increasing demand in palm oil has provoked growers to augment their oil palm product through land expansion and intensification. Land expansion is preferable due to less effort and low costs however it is not recommended due to negative impacts caused by deforestation. Therefore, intensification is suggested using best practices and good plant material. Replanting is one of alternatives to improve oil palm production when best practices are no longer effective due to bad plant material. Replanting become a challenging issue for oil palm smallholders because of their limited acces to information, inputs and fund. The aim of this study is to analyse farmers’ perception on replanting program. A survey on farmers’ perception on replanting was conducted using likert-scale method. The result show that the farmers have positive thinking on replanting program. However, they still uncertain when to implement the replanting program. Some farmers consider that the existing production still an important source of household income.   Key words:  Independent Smallholders, Replanting, Perception, Sustainable Production